2018
DOI: 10.1177/0284185118774913
|View full text |Cite
|
Sign up to set email alerts
|

Dependence of intravoxel incoherent motion diffusion MR threshold b-value selection for separating perfusion and diffusion compartments and liver fibrosis diagnostic performance

Abstract: For segmented-unconstrained analysis, the selection of threshold b-value = 60 s/mm improves IVIM differentiation between healthy livers and fibrotic livers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
37
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 20 publications
(40 citation statements)
references
References 30 publications
3
37
0
Order By: Relevance
“…Thus, our results further support the adoption of threshold b of 60 s/mm 2 [17][18][19]. Segmented fitting with threshold b of 60 s/mm 2 are further presented in Fig-3; and used as primary results for this study.…”
Section: Methodssupporting
confidence: 76%
See 1 more Smart Citation
“…Thus, our results further support the adoption of threshold b of 60 s/mm 2 [17][18][19]. Segmented fitting with threshold b of 60 s/mm 2 are further presented in Fig-3; and used as primary results for this study.…”
Section: Methodssupporting
confidence: 76%
“…For part-2, starting from non-zero very low b-value, the relationship between DWI signal and b-value follows a biexponential decay [5,10,[15][16][17][18]. It has also been empirically showed that, as compared with the commonly used threshold b-value of 200 s/mm 2 for segmented fitting, the threshold b-value of 60 s/mm 2 to separate slow and fast components performed better in separating normal livers and fibrotic livers [17,18,19]. Liver physiological MRI measures may differ in males and females and may differ in young adults and older adults [20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…The optimal threshold b-value for liver IVIM analysis remain undecided. In our recent report it was empirically demonstrated that compared with the commonly increases the mean distance between healthy liver datapoints cluster and fibrotic liver datapoints cluster (23). This study, using a new set of healthy volunteers and patients' data, confirmed the superiority of using threshold b-value =60 s/mm 2 instead of threshold b-value =200 s/mm 2 for detecting liver fibrosis.…”
Section: Discussionsupporting
confidence: 63%
“…The same as our last study (15), among the three IVIM parameters, PF also showed best diagnostic performance in this study. According to previous estimation, Dfast should be the most sensitive parameter for liver fibrosis evaluation (14,15,23); however, precise measurement of Dfast is difficult and this current study did not include sufficient very low b-values for precise Dfast quantification (33,34). More b-values and applying an optimized b-value distribution shall be able to reduce errors in IVIM parameter estimation.…”
Section: Discussionmentioning
confidence: 89%
“…On the other hand, with empirical data analysis Wang et al reported that a threshold b-value of 60 s/mm 2 improves differentiation between healthy livers and fibrotic livers. 28,29 In the current study, for comparison purposes the most commonly used 200 s/mm 2 was adopted. Different numbers of slices were included for each scan's analysis, and this could have slightly influenced the IVIM parameter values ( Supplementary Document 4).…”
Section: Discussionmentioning
confidence: 99%